Assessing the use of linear regression analysis in examining service quality and customer satisfaction relationship in premium casual restaurants (PCR) in Subang Jaya (Klang Valley) Malaysia - Saad, Mazni; Abukhalifeh, Alaa Nimer; Slamat, Syafiq Syaheer; TengkuYacob, Tengku Nor Farah Farhanah (GMP Press & Printing Co., 2020)
Many urban Malaysians are attracted to the moderately-priced food that is usually served in a casual atmosphere. Its popularity has given rise to its potential business in the foodservice industry. The sudden increase in the number of Premium casual restaurants (PCR), however, creates a stiff competition which has resulted not only in a bad turnover of customers but also in businesses closing abruptly. Another reason for such closures is also the dissatisfied customers who experience poor quality service at these dining restaurants. Thus, the current study aims to examine the relationship between Service Quality (SERVQUAL) and customer satisfaction at (PCR). A total of 380 questionnaires distributed and yielded a response rate of 53 percent. The SERVQUAL model contributed 76 percent of the variance in the customers’ satisfaction level among those who dined in the restaurants. The overall results show that in a highly competitive business environment, customers' evaluation of Service Quality and customer satisfaction is critical to the service restaurants' survival. The management must, therefore, focus on these most crucial factors that have enhanced service standards of future research.